Study of Arabic Translation of Her Eyes According to Bremen’s Deconstructive Method - Tayebeh Amirian (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Translation criticism, based on the patterns of cognitive translations, is a criterion to describe the translation function in the target language by preserving literature and understanding the meaning of the source language. The validity of the translation of the novel will also be measured and represented with meticulous awareness of the shortcomings and its positive features according to the principles of translation evaluation models. Antone Breman, whose basis of his translational viewpoint is based on the source text, explains the twelve deforming tendencies between the source, target language named “deconstructive method” or “distortion factors”. According to this theory, when the number of changing trends in the translation process is more significant, the translator has distorted the original text more. In this study, we want to consider the perspective of Bremen’s deconstructive tendencies with respect to the alien text and foreign, Arabic translation called “Aynaha” by Ahmad Musa of “Her Eyes” written by Bozorg Alavi. The main focus of this research is to review the dominant trends in text change by translator mentioning to citing the evidence and proposed translation. Findings of the study confirm six trends of twelve Bremen deconstructive tendencies, and it claims that the translator, according to his own taste, has made changes in translation, and he was not loyal to the source text.